Mehr Nachhaltigkeit im deutschen Leitindex DAX - Volker Brühl (Wirtschaftsdienst, 2020)
Im Rahmen der Aufarbeitung des Wirecard-Skandals wird auch eine Änderung der Kriterien zur Aufnahme in den deutschen Leitindex DAX diskutiert. Die bislang von der Deutschen Börse vorgesehenen Maßnahmen gehen in die richtige Richtung, sind aber nicht weitreichend genug. Es bedarf eines deutlichen Zeichens, dass sich künftig nur solche Unternehmen für den DAX qualifizieren können, die ein zumindest befriedigendes Maß an Nachhaltigkeit gemessen durch einen ESG-Risk-Score (Environment, Social, Governance) in ihrer Geschäftstätigkeit erreichen. Eine Simulation verdeutlicht, dass nach ESG-Kriterien seit langem kritisch betrachtete Unternehmen dem DAX nicht mehr angehören würden. Damit könnte mehr Kapital in nachhaltig wirtschaftende Unternehmen und Sektoren fließen. – – In the course of analysing the causes and consequences of the Wirecard scandal, a discussion about the potential reform of the German lead stock market index DAX is underway. The initial proposals presented by Deutsche Börse are moving in the right direction but are not farreaching enough. A clear signal is needed to indicate that future constituents of the DAX are obliged to meet at least a satisfactory level of sustainability, measured by an ESG (Environment, Social, Governance) Risk Score for the respective business activities. A simulation presented in this article demonstrates that some current members would no longer qualify for the DAX. Adding an ESG Risk Score to the current index selection criteria would set strong incentives for companies to gear their business strategies towards greater sustainability. Redesigning major stock indices to include sustainability aspects could ultimately play an important role in having more capital allocated to sustainably operating companies and sectors.
Keywords: G1; G2; 330